Engineering of Surface Energy of Cell‐Culture Platform to Enhance the Growth and Differentiation of Dendritic Cells via Vapor‐Phase Synthesized Functional Polymer Films. Issue 17 (17th March 2022) - Lee, Minseok; Chun, Dongmin; Park, Seonghyeon; Choi, Goro; Kim, Yesol; Kang, Suk‐Jo; Im, Sung Gap
Abstract: Although the dendritic cell (DC)‐based modulation of immune responses has emerged as a promising therapeutic strategy for tumors, infections, and autoimmune diseases, basic research and therapeutic applications of DCs are hampered by expensive growth factors and sophisticated culture procedures. Furthermore, the platform to drive the differentiation of a certain DC subset without any additional biochemical manipulations has not yet been developed. Here, five types of polymer films with different hydrophobicity via an initiated chemical vapor deposition (iCVD) process to modulate the interactions related to cell–substrate adhesion are introduced. Especially, poly(cyclohexyl methacrylate) (pCHMA) substantially enhances the expansion and differentiation of conventional type 1 DCs (cDC1s), the prime DC subset for antigen cross‐presentation, and CD8 + T cell activation, by 4.8‐fold compared to the conventional protocol. The cDC1s generated from the pCHMA‐coated plates retain the bona fide DC functions including the expression of co‐stimulatory molecules, cytokine secretion, antigen uptake and processing, T cell activation, and induction of antitumor immune responses. To the authors' knowledge, this is the first report highlighting that the modulation of surface hydrophobicity of the culture plate can be an incisive approach to construct an advanced DC culture platform with high efficiency, which potentially facilitates basic research and the development of immunotherapy employing DCs. Abstract : The surface property of culture substrate can be simply and precisely modulated by coating extremely conformal polymers via initiated chemical vapor deposition. The prominent transition of cell adhesion can be induced during the dendritic cell (DC) differentiation subject to surface hydrophobicity. In particular, expansion of DCs and preferential differentiation of cDC1 showing bona fide DC functions can be substantially enhanced in the poly(cyclohexyl methacrylate).